2019
DOI: 10.1111/acer.14232
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Theory of Planned Behavior in the Prediction of Alcohol‐Induced Blackout Intention and Frequency

Abstract: Background: This study examined the Theory of Planned Behavior (TPB) as an explanatory model for alcohol-induced blackouts among college students. Blackouts are periods of time wherein individuals continue to function and engage in their social environment but do not remember it as a result of consuming large quantities of alcohol. Social cognitive factors posited within TPB, such as perceived norms and personal attitudes toward alcohol consumption, are reliable predictors of alcohol use and related problems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Specifically, the Theories of Reasoned Action and Planned Behavior-more recently formulated as the Integrative Model (Fishbein, 2008)-suggest that intention to engage in a behavior is the most important and proximal determinant of behavior, and intentions are influenced by one's outcome expectancies for, and attitudes toward, normative perceptions of, and confidence in their ability to control that behavior. Consistent with this theory, research recently demonstrated that intentions to experience blackout are associated prospectively with the frequency of actual blackout experiences (DiBello, Miller, Merrill, & Carey, 2020). Thus, understanding the types of young adults who intend to engage in blackout levels of drinking and what motivates them to experience blackouts may help providers tailor intervention efforts to the context of drinking most relevant to this highrisk subgroup of drinkers.…”
mentioning
confidence: 85%
“…Specifically, the Theories of Reasoned Action and Planned Behavior-more recently formulated as the Integrative Model (Fishbein, 2008)-suggest that intention to engage in a behavior is the most important and proximal determinant of behavior, and intentions are influenced by one's outcome expectancies for, and attitudes toward, normative perceptions of, and confidence in their ability to control that behavior. Consistent with this theory, research recently demonstrated that intentions to experience blackout are associated prospectively with the frequency of actual blackout experiences (DiBello, Miller, Merrill, & Carey, 2020). Thus, understanding the types of young adults who intend to engage in blackout levels of drinking and what motivates them to experience blackouts may help providers tailor intervention efforts to the context of drinking most relevant to this highrisk subgroup of drinkers.…”
mentioning
confidence: 85%
“…Similarly, in a sample of 350 undergraduate students (age 18–29) reporting past-year blackouts, 39% indicated that they had intended to experience a blackout in the past 30 days and 31% indicated that they intended to experience a blackout in the next 30 days (Miller et al, 2020). Importantly, a follow-up of these participants 1 month later found that blackout intentions predicted subsequent blackouts (DiBello et al, 2020). Although this prior research has established that some individuals express intentions to black out, attempts to more deeply understand such intentions are lacking.…”
Section: Intentions and Willingness To Black Outmentioning
confidence: 99%
“…Theirs is the most cited article published before 2000 in the Journal of Personality & Social Psychology (Quiñones-Vidal et al, 2004). Mediation models, especially the Theory of Planned Behaviors (TPB; Ajzen, 2002), have been frequently applied to study alcoholic behaviors and alcoholism in primary studies (e.g., Conner et al, 1999;DiBello et al, 2020;Hasking & Schofield, 2015).…”
Section: Synthesizing Indirect Effects In Mediation Models With Meta-mentioning
confidence: 99%